How Much Are Individuals Left Behind in Central and Eastern Compared to Western European Countries? A Fuzzy Comparative Analysis. - Bárcena-Martín, Elena María; García-Pardo, Francisca; Pérez-Moreno, Salvador Jesús (My University, 2023)
This paper examines the extent to which individuals of Central and Eastern European (CEE) countries are left behind compared to individuals from Western European (WE) countries based on a fuzzy approach applied to a multidimensional setting. Three decades after transitions from non-democratic regimes to liberal democracy and from centrally planned economies to market economies of these countries, we observe a certain process of convergence between both blocs of countries over the period 2007-2019, essentially as a result of the decrease in the level individuals are left behind in the CEE countries, reaching similar levels to WE countries. Furthermore, we reveal significant disparities across CEE countries, ranging from Czech Republic, Slovenia and Slovakia, where citizens are less left behind, to Bulgaria, Lithuania and Romania, with higher levels of leaving behind. Differences in the degree individuals are left behind along the income distribution and by sociodemographic characteristics are also analysed, highlighting dissimilarities of lagging socioeconomic profiles across countries.
Keywords: Política económica - Europa oriental; Postcomunismo - Aspectos sociales; Central and eastern European countries; Fuzzy set; Left behind; Income; Material deprivation; Work intensity